Neorealism’s Power and Restraint: A Tribute to Waltz on his 100th Birthday - Randall Schweller (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
Kenneth Waltz constructed a pure theory of international politics by isolating structural from unit-level causes. Today’s return of great-power politics signals the persistent relevance of Waltz’s notion of patterns and regularities driven by structural-systemic forces. We have entered an unbalanced bipolar world, in which America still exceeds China in every important category of national power but the gap is narrowing. The relative-power trajectories of the two sides now frames the structural dynamics of their relationship, and how others perceive and calculate their strategic competition. No longer occupying a position of “primacy” either globally or in the Asian Pacific region, the United States now tends to exaggerate, not underestimate, the perceived threat from China in the economic and security realms. More broadly, the world is transitioning from hegemonic order to global disharmony and a restored balance of power—what I refer to as a “Dissent” phase of history. In this phase, disruption of global stability comes not only from the emergence of a counter-hegemonic alliance, which begins to voice its dissatisfaction with the status-quo order and underlying social purpose. It also comes from the hegemon itself, which behaves in ways that undermine its own order—an order that it now sees as not only unprofitable but a drain on its wasting assets through sponging allies and the exorbitant costs of delivering global public goods.